Analisis Hukum Tentang Pemanggilan Anggota Dpr Yang Diduga Melakukan Tindak Pidana Pasca Keluarnya Putusan Mahkamah Konstitusi Nomor: 76/Puu-Xii/2014 - Wahyu Wahyu saputra; Ridham Priskap (Universitas Jambi, Fakultas Hukum, 2022)
It is deemed necessary to examine the mechanism for taking action against DPR members who commit acts of corruption based on several considerations, namely first, that the DPR RI is currently in the highest position in the list of corruption cases. Second, efforts to eradicate corruption are a shared commitment that must be a priority. Based on this, the writer draws two formulations of the problem, namely How is the process of summoning members of the DPR by law enforcement officials after the issuance of the Constitutional Court's decision Number 76/PUU-XII/2014? And what are the legal implications of the decision of the Constitutional Court Number 76/PUU-XII/2014 on the process of summoning members of the DPR who are suspected of committing criminal acts? Furthermore, the author uses a normative juridical research method, so that two main points are obtained, namely, first, Article 245 before being submitted to the Constitutional Court, when law enforcement officials will conduct an examination of members of the DPR must obtain written permission, which means that the investigators will experience difficulties. stating that the examination must have a presidential permit does not answer the substance of the case application, because article 245 before being submitted to the Constitutional Court contains an examination permit from the MKD. Meanwhile, the decision of the case contains permission from the president. Keywords: Legal Analysis, DPR, Corruption